(untitled) (Historia, 2021)
This paper seeks to demonstrate the value of oral traditions as heritage that needs to be preserved paying particular attention to the traditions concerning the Shona people of Zimbabwe. It adopts a historiographical approach, which attempts to examine the way the traditions have been collected by various people and the reasons for collecting them as well as the various interpretations that they have been given by successive generations of scholars. It is on the strength of this background that the article suggests some methodological solutions.